Employer, Insurer, and Industry Perspectives on Patient-Centered Comparative Effectiveness Research Final Report - Concannon, Thomas W. (RAND Corporation, 2015)
On behalf of the Patient-Centered Outcomes Research Institute (PCORI), RAND conducted a series of focus groups to explore the views of payers, purchasers, and industry stakeholders on comparative effectiveness research (CER). This report describes stakeholders' health-related decisions, information needs, and views on being involved in CER. Key themes emerging from the discussions are presented, along with implications for PCORI's future work.